Phytonutrients 2012
DOI: 10.1002/9781118253649.ch1
|View full text |Cite
|
Sign up to set email alerts
|

Plant Foods and Health

Abstract: Table 1.2 Categorisation of plant derived foods and drinks Group Examples Fruits Tree Fruits Apples, pears, plums, apricots, peaches, cherries, citrus fruit, dates, pineapple, mango, papaya, fig, olive Soft fruits Strawberries, raspberries, blackberries, cranberries, currants Other Melons, grapes, kiwi, bananas Vegetables Root crops* Potatoes, sweet potatoes, yam, cassava Carrots, turnips, swedes, parsnips Cabbage family Cabbage, broccoli, Brussels sprouts Onion family Onions, leeks, garlic Salad vegetables Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 164 publications
(176 reference statements)
0
3
0
1
Order By: Relevance
“…Cantín et al (2009b) obtuvieron diferentes contenidos de vitamina C en frutos de pulpa blanca (4,8 mg/100 g de peso fresco) y de pulpa amarilla (3,5 mg/100 g de peso fresco); los cuales se encuentran dentro del rango mencionado anteriormente. Según Saltmarsh et al (2003) los frutos son una fuente importante de vitaminas, minerales y compuestos antioxidantes, estos compuestos ayudan a reducir el riesgo de enfermedades cró-nicas (Buttriss, 2012). Una de las principales razones que explica la gran aceptación de los frutos de durazno entre los consumidores, está relacionada con sus propiedades organolépticas, nutricionales (Brandi et al, 2011) y medicinales (Morales, 2011).…”
Section: Cambios En Azúcares Solubles Y áCidos Orgánicosunclassified
“…Cantín et al (2009b) obtuvieron diferentes contenidos de vitamina C en frutos de pulpa blanca (4,8 mg/100 g de peso fresco) y de pulpa amarilla (3,5 mg/100 g de peso fresco); los cuales se encuentran dentro del rango mencionado anteriormente. Según Saltmarsh et al (2003) los frutos son una fuente importante de vitaminas, minerales y compuestos antioxidantes, estos compuestos ayudan a reducir el riesgo de enfermedades cró-nicas (Buttriss, 2012). Una de las principales razones que explica la gran aceptación de los frutos de durazno entre los consumidores, está relacionada con sus propiedades organolépticas, nutricionales (Brandi et al, 2011) y medicinales (Morales, 2011).…”
Section: Cambios En Azúcares Solubles Y áCidos Orgánicosunclassified
“…According to data from the National Food Survey and subsequently the National Diet and Nutrition Survey for the UK, the mean (SD) general consumption of vegetables, excluding potatoes and pulses, has remained at approximately 994 (42) g (person week) −1 since 1974 and consumption of all types of fruit has remained at approximately 679 (49) g (person week) −1 for the same period (Buttriss, ). However, the most marked observation has been the near linear increase in fruit juice consumption, which has risen more than 10‐fold from 30 g (person week) −1 in 1974 to 385 g (person week) −1 in the latest NDNS survey.…”
Section: Introductionmentioning
confidence: 99%
“…() suggested that this dietary pattern may be beneficial to health because of the relatively high level of antioxidants and unsaturated fatty acids. But over recent years, evidence to support the role of antioxidants in chronic disease has weakened (Buttriss ).…”
Section: Methodsmentioning
confidence: 99%